THE URGENCY OF VILLAGE FUNDS IN INCREASING AGRICULTURAL PRODUCTIVITY IN INDONESIA - Egidius Fkun; Eva Yuniarti Utami; Abdurrahim; Hakkul Bahiz Mahdani; Shohib Muslim (ITB AAS Indonesia Surakarta, 2025)
Abstract This study is a qualitative study with a descriptive approach, namely an approach that will describe the main topic in this article, namely the use of village funds to increase agricultural productivity. The data used in this article is secondary data that researchers obtain from indirect sources but its truth is unquestionable because it has been strictly verified and has good credibility. The data researchers obtain from scientific journals. Books, websites, and other sources that are commonly used in every study. The data obtained is collected, combined, selected, reduced, and conclusions are drawn. The result in this article show that the use of village funds to increase agricultural output of rural communities while improving the welfare of rural communities is in line with the law on villages and its derivative laws and regulations. This is also believed to be able to improve the welfare of rural communities because by increasing agricultural output, it can increase rural community income, primary, tertiary, secondary, and primary food needs can be met, and ultimately the welfare of rural communities will increase. This article is one of a series of planning stages that will hopefully increase in the implementation and reporting stages in the future. Keywords : Village Fund, Agricultutral Productivity, Village